"I am Fatima Zunayburia and You Are Mustafa Kindil": Writing Feminist History and National Historiography in Morocco - Kozma, Liat (Jama'a: an Interdisciplinary Journal of Middle East Studies, 2000)
Feminist research often views nationalist and feminist historiographies as two essentially unchanging isolated entities. In this article, I examine Moroccan national historiography as a site where various versions of the past have been in a continuous contest, leading to transformations in the dominant historical narrative. First, I look at Maroccan feminist historiography in the context of the socio-political realities of the 1980s and the 1990s, which enabled the visibility of women as a historical category. I then show how the struggle for national independence was used within this feminist historiography for the formation of an indigenous genealogy of feminist activity, aiming at achieving cultural legitimacy for an egalitarian ideology. Finally, I examine how tension and dialogue between these two historiographies led to the incorporation of women into the dominant nationalist historiography. At the same time, the dissent embedded in the feminist historiography was undermined by its incorporation into the dominant historiography.